Papers - Critical Studies of a Modified Ledebur Method for Determination of Oxygen in Steel (With Discussion) - B. M. Larsen; T. E. Brower (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
An increasing amount of attention is being paid to the possible influence of oxygen, in its several modes of occurrence in steel, upon some of the properties of the metal; but clearly investigations along this line are unlikely to yield significant results until reliable analytical methods for the determination of oxygen have been established. This paper presents some results of a study of an improved Ledebur method which aims to determine a definite portion of the oxygen; namely, that which presumably is present in diffusible form in the solid steel. These more or less preliminary results lead us to believe that the oxygen so determined has some significance; their presentation at this time will, we hope, stimulate discussion of, and focus attention upon, certain rather neglected aspects of the problem. Considerable work has been done recently on methods of estimating inclusions and on the vacuum-fusion method for oxygen; with results which, however, are of somewhat questionable significance. It is commonly presumed that the oxygen in a bath of molten steel in a furnace is present partly as a separate phase consisting of suspended particles of oxides or silicates, partly in solution, the latter being probably the more important. Upon addition of a deoxidizer, it reacts with some portion of the dissolved oxygen and precipitates it as additional suspended particles; the oxygen not eliminated in this way, which remains in solution in the liquid steel, may be regarded indifferently either as dissolved oxygen or as dissolved FeO. When the steel is poured, some of the suspended particles rise towards the surface, others remain trapped in the finished steel, appearing as nonmetallic inclusions in amounts corresponding usually to about 0.01 to 0.03 per cent Oz in the steel. The dissolved oxygen may be partly eliminated as CO during freezing of the ingot, but some remains either in solution or in part precipitated as FeO. Finished steels may thus contain oxygen in several forms: (1) In non-metallic inclusions which are probably quite insoluble in the solid metal at all temperatures; (2) in solid solution which at lower temperatures may be supersaturated; (3) in FeO particles produced by relief of this